Gender Issues in English Language Teaching: Views from Turkey - Ordem Eser; Ulum Ömer Gökhan (Acta Educationis Generalis)
Introduction: Research into gender diversity and equality of gender in humanities has been mounting since 1960s, when post-modernism and post-structuralism emerged as a reaction to metanarratives of modernization. Methods and approaches in ELT also arose in the same years. However, queer and LGBT identities were intentionally ignored in ELT discipline and departments, although English as a lingua franca was already hailed in the inner circle. This study aimed to unearth the views of young adult learners of English regarding LGBT. Two data collection instruments were administered. A standard scale composed of 21 items that measure homosexuality attitudes was given to the participants (N= 113). In addition, a semi-structured interview was prepared to elicit the participants’ views (N=12). The results of the study show that most of the participants showed a positive attitude towards LGBT. However, they reported that this topic was never addressed in ELT settings.